Therapy Dogs' and Handlers' Behavior and Salivary Cortisol During Initial Visits in a Complex Medical Institution: A Pilot Study - Clark, Stephanie D.; Smidt, Jessica M.; Bauer, Brent A. (Frontiers in Veterinary Science, 2020)
Therapy dogs provide health benefits for individuals who suffer from illnesses, such as dementia, depression, loneliness, and aggression. Therapy dogs’ impact on human health has been thoroughly studied; however, studies on dog welfare have been limited. The body language of dogs is poorly understood and can lead to dog owner-directed aggressive. Communication plays a vital role to be a cohesive therapy team. The purpose of this study was to assess perceived stress and cortisol concentrations in therapy dogs and their handlers during the first three onboarding visits in a hospital setting. Moreover, the study aimed to investigate if, while in an over-stimulating environment, a therapy dog handler can observe their dog’s body language and correlate such observations to their dog’s stress. Nine therapy dog teams from Mayo Clinic’s Caring Canine Program volunteered for this study. A baseline salivary cortisol was collected from the handler and therapy dog each day of the visits. Once the team arrived, a pre-visit salivary cortisol was collected from the handler and therapy dog and afterwards, a post-visit salivary cortisol. Handlers were also asked to fill out a perceived stress survey on their stress and their therapy dog’s. Behavior was documented by a staff member and the handler. For each visit, the therapy dogs were at the hospital on average 47 minutes and visited with 9 people. There was significant correlation (P = 0.02) between the owner’s perceived stress of their therapy dog and the dog’s salivary cortisol concentrations. The handlers noted medium to high stress and those dogs had higher cortisol concentrations post-visit. There was no significant difference in salivary cortisol for the handler and therapy dog over the course of the three visits and comparing pre- and post-visit. Overall the dogs displayed mixed behaviors with the three most reported being panting, lip licking, and yawning. Results suggest that the handlers and therapy dogs maintained their welfare state throughout the visits and throughout the onboarding process.